IMPLEMENTASI TEORI PERUBAHAN SITUASI (NAZHARIYAT AL-ZHURUF AL-THARI’AH) DALAM PENYELESAIAN KASUS PELANGGARAN HAK SEWA-MENYEWA TANAH BENGKOK HASIL LELANG DI INDONESIA - Alfi Ma’rifatun Nisa (JIL : Journal of Indonesian Law, 2021)
Leasing a tanah bengkok is one part of the muamalah practice, where violations are often found by one party, causing a change in the situation (condition) in the implementation of the contract. This encourages the agreement makers to immediately follow up on changes in these conditions so that no party is harmed. Cases of violation of rights in the lease of tanah bengkok with the auction system in Indonesia are generally motivated by the existence of old tenants who do not carry out their obligations according to the contents of the agreement, namely exceeding the time limit in returning the tanah bengkok. Then the solution is to free the old tenant to manage the tanah bengkok outside the rental period, so that it causes the next tenant to not get the right to cultivate the tanah bengkok. For that, there must be a solution to overcome this. The fiqh scholars have thought of several rules or thoughts to overcome these things that cannot be prevented. Therefore, in Islam, the term theory of situation change (Nazhariyat Al-Zhuruf Al-Thari'ah) is known, which is a theory that aims to overcome these things that cannot be prevented.